Pengistilahan Al-Waqful ’Ajil Biqardhil Hasan (WAQH) sebagai satu instrumen kewangan sosial bagi membiayai projek berkaitan kepentingan awam - Othman, Mohd Amim (Persatuan Ekonomi Pengguna dan Keluarga Malaysia, 2024)
‘Al-Waqful ’Ajil Biqardhil Hasan (WAQH) is a term referring to a benevolent loan transaction and a capital repayment based on a deferred waqf donation at a specified period as agreed by the contracting parties. From the aspect of implementation, WAQH is a crowdfunding project which collaborates three parties, namely the borrower of capital without benefit (qardhul hasan) and the payer of the loan (muwaqif) with the project taken care of by a third party (executor) at a set rate of pay. The benefit to the borrower is a reward granted by Allah SWT based on the amount of loss of savings profit due to the transfer of cash from the borrower's savings account to the executor's account. While the benefit to the donor is the reward from the value of the cash transfer from the donor’s savings account to the executor's account to redeem the debt given by the capital loanee. Practically three (3) WAQH projects have been implemented involving waqf donations totalling nearly RM900,000. However, since WAQH is a new social financial engineering instrument, there is a need to term WAQH to make it easier for the general public to understand about the project that will be implemented. Based on the implementation of several projects using WAQH instrument, the project is found to be well-managed and the cost of goods is not affected by the increase in inflation because the construction goods and wages have been paid and determined in advance and the possibility of failure of a project can be avoided. In addition, the level of confidence amongst community in providing waqf fund donations is higher than the current concept of waiting for waqf funds to be collected before implementing the desired project. This is because the project which will receive waqf donations has been implemented and is almost ready. The positive impact from the progress of the project which follows the schedule creates enthusiasm amongst the donor to pace up and get the limited waqf lot offered by the executor. Currently, WAQH's main focus is on implementing projects related to social finance which benefit the community such as mosque and musolla development, as well as public facilities such as toilets, air conditioners and bridges.